Added Value Analysis of Bandeng Fish (Chanos chanos) Amplang Business in Babulu Laut Village, North Penajam Paser Regency (Indonesian Journal of Aquaculture Medium, 2024)
Bandeng fish amplang processing in Babulu Laut Vilage is still classified as a small household business, with 7 amplang processors in Babulu Laut Village. This research was conducted to determine the value added of the bandeng fish amplang business in Babulu Laut Village. The number of respondents was 7 people, so the researcher took the entire population as a sample (census). The results showed that the added value of raw bandeng fish processed into amplang was Rp. 198,553 per kg with a value added ratio of 66%. This value added ratio is considered high because it is more than 10%. The profit margin of the bandeng fish amplang was Rp. 270,865 with a profit of 69 that had been distributed to each individual such as labor income of 4% and other input contributions of 27%.
Keywords: Amplang Bandeng; Babulu Laut Vilage Fish; Value Added